(untitled) (Yupana, 2021)
This article aims to analyze the Tactile Model (MT) based on the perspective of Universal Design for Learning (DUA). MT is composed of pieces and Jefferson’s Random Walks Teaching Sequence (SE–PAJ), which addresses the concept of chance. The theoretical discussion was developed in two stages, from which in this article was evaluated only the third task of SE–PAJ and the pieces involved. The analytical categories of first stage were the checkpoints of three guidelines of principle 1, and in the second stage, only the guidelines of principles 2 and 3. The results seem to indicate that this task and the pieces satisfactorily meet the principles and guidelines of the DUA to approach the concept of chance. For example, the guideline «Clarify terminology and symbols» was included because before the development of this task, students had possibility to experience situations in previous tasks which promoted familiarization with the terminology, emphasizing the use of terms such chance instead probability, and is also associated with the concept of fair. It is expected that this article will contribute to studies involving the proposition of teaching materials from the perspective of DUA and, therefore, support a more realistic and integrative inclusion of all students.